A Program for Master of Science in Environment and Natural Resources (MENR) - Kabale University (Kabale University, 2022)
In terms of policy context, this program is structured to meet the basic requirements that fit into Sustainable Development Goals (SDGs), African Union Vision 2063, Uganda Vison 2040, Uganda national development plan. According to UN Sustainable Development Goals (SDG), the Goals and targets will stimulate action over the next 15 years in areas of critical importance for humanity and the planet. It states, “We are determined to end poverty and hunger, in all their forms and dimensions, and to ensure that all human beings can fulfil their potential in dignity and equality and in a healthy environment and determined to protect the planet from degradation, including through sustainable consumption and production, sustainably managing its natural resources and taking urgent action on climate change, so that it can support the need of the present and future generations” Goal 15 is to protect, restore and promote sustainable use of terrestrial ecosystems, sustainably manage forests, combat desertification, and halt and reverse land degradation and halt biodiversity loss. The Msc. ENR programme is to produce mid-career level scientists to meet the immediate demand for environment and resource management specialists. This will be fulfilled through working closely with rural farmers, research and educational programmes that link advances in fundamental and applied biological sciences to indigenous and contemporary development issues. The goal of this programme is to establish a new training programme of management in the environment and natural resources, that will use an integrated, multidisciplinary and participatory tools and methodologies to produce quality mid-career level training to scientists to enable them lead efforts to increase the productivity of rural resources, biodiversity, reduce poverty and hunger and combat climate change. This will be achieved through a joint effort and interaction of technical expertise in rural resource management and planning, rural farming communities and national and district planning authorities. Collaborative arrangements with various universities, UN agencies, and research institutions will be made in order to increase the exchange of ideas and adaptive techniques and methodologies. The programme objectives are to produce graduates that will be able to: i. Apply theoretical knowledge in natural resources and environment to promote sustainable production. ii. Utilize their skills to analyse relationships between agricultural production, natural resource depletion, climate change, pollution and land degradation and develop innovative methods and mitigate their effects. iii. Promote professional development through multidisciplinary approaches to solve challenges in environment and natural resources.